THE INFLUENCE OF PRICE, PRODUCT QUALITY AND PROMOTION ON CUSTOMER LOYALTY THROUGH CUSTOMER SATISFACTION AS A CONNECTION VARIABLE IN CUSTOMER HYPERMART CYBERPARK KARAWACI, TANGERANG, BANTEN - Dennis Vidina Natawijaya; Widi Dewi Ruspitasari; Yunus Handoko (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2023)
The purpose of this study was to determine the effect of price, product quality, and promotion on customer loyalty mediated by customer satisfaction. The research population is Hypermart Cyberpark Karawaci customers with a sample of 100 respondents using an accidental sampling technique. The analysis technique uses Partial Least Square (PLS). The test instruments used are validity and reliability test, outer model construction test, R-Square Inner Model, Q-Square and GoF test, and bootstrapping hypothesis test, the results show that price has an effect on customer loyalty, product quality and promotions have no effect on customer loyalty, price and promotion have no effect on customer satisfaction, product quality has an effect on customer satisfaction, customer satisfaction has a significant effect on customer loyalty, price, product quality, and promotion have no effect on customer loyalty through customer satisfaction.